Dogmatic's Impact of Circumstances Concomitant Formulating the Finalist Concept of Pure Normative Culpability and its Confront with the Modern Functional- Systemic Perspective - Fonseca, Ana Clara Montenegro (2016)
The paper analyzes normative aspect (finalist) and functionalist (systemic) of culpability, checking the influence of concomitant circumstances, from Reinhart Frank. Theoretical study with bibliographic procedure is based on the essence and evolution of culpability along with theoreticians of modernity to understand the functional culpability. The research is divided into: etiological basis of the concept of culpability; theories of culpability; impact of concomitant circumstances; perception of funcional culpability. Demonstrate, so how modern theorists interpret this institute and confront such an understanding with the finalists fundamentals, noting affinity or disagreement of the practical application of the institute with that theory